Streptococcus pneumoniae Eradicates Preformed Staphylococcus aureus Biofilms through a Mechanism Requiring Physical Contact - Khan, Faidad; Wu, Xueqing; Matzkin, Gideon L.; Khan, Mohsin A.; Sakai, Fuminori; Vidal, Jorge E. (Frontiers in Cellular and Infection Microbiology, 2016)
Staphylococcus aureus (Sau) strains are a main cause of disease, including nosocomial infections which have been linked to the production of biofilms and the propagation of antibiotic resistance strains such as methicillin-resistant Staphylococcus aureus (MRSA). A previous study found that Streptococcus pneumoniae (Spn) strains kill planktonic cultures of Sau strains. In this work, we have further evaluated in detail the eradication of Sau biofilms and investigated ultrastructural interactions of the biofilmicidal effect. Spn strain D39, which produces the competence stimulating peptide 1 (CSP1), reduced Sau biofilms within 8 h of inoculation, while TIGR4, producing CSP2, eradicated Sau biofilms and planktonic cells within 4 h. Differences were not attributed to pherotypes as other Spn strains producing different pheromones eradicated Sau within 4 h. Experiments using Transwell devices, which physically separated both species growing in the same well, demonstrated that direct contact between Spn and Sau was required to efficiently eradicate Sau biofilms and biofilm-released planktonic cells. Physical contact-mediated killing of Sau was not related to production of hydrogen peroxide as an isogenic TIGR4spxB mutant eradicated Sau bacteria within 4 h. Confocal micrographs confirmed eradication of Sau biofilms by TIGR4 and allowed us to visualize ultrastructural point of contacts between Sau and Spn. A time-course study further demonstrated spatial colocalization of Spn chains and Sau tetrads as early as 30 min post-inoculation (Pearson’s coefficient >0.72). Finally, precolonized biofilms produced by Sau strain Newman, or MRSA strain USA300, were eradicated by mid-log phase cultures of washed TIGR4 bacteria within 2 h post-inoculation. In conclusion, Spn strains rapidly eradicate pre-colonized Sau aureus biofilms, including those formed by MRSA strains, by a mechanism(s) requiring bacterium-bacterium contact, but independent from the production of hydrogen peroxide.